APOL1 variant-expressing endothelial cells exhibit autophagic dysfunction and mitochondrial stress - Blazer, Ashira; Qian, Yingzhi; Schlegel, Martin Paul; Algasas, Huda; Buyon, Jill P.; Cadwell, Ken; Cammer, Michael; Heffron, Sean P.; Liang, Feng-Xia; Mehta-Lee, Shilpi; Niewold, Timothy; Rasmussen, Sara E.; et al. (Frontiers in Genetics, 2022)
Polymorphisms in the Apolipoprotein L1 (APOL1) gene are common in ancestrally African populations, and associate with kidney injury and cardiovascular disease. These risk variants (RV) provide an advantage in resisting Trypanosoma brucei, the causal agent of African trypanosomiasis, and are largely absent from non-African genomes. Clinical associations between the APOL1 high risk genotype (HRG) and disease are stronger in those with comorbid infectious or immune disease. To understand the interaction between cytokine exposure and APOL1 cytotoxicity, we established human umbilical vein endothelial cell (HUVEC) cultures representing each APOL1 genotype. Untreated HUVECs were compared to IFNɣ-exposed; and APOL1 expression, mitochondrial function, lysosome integrity, and autophagic flux were measured. IFNɣ increased median APOL1 expression across all genotypes 22.1 (8.3 to 29.8) fold (p=0.02). Compared to zero risk variant-carrying HUVECs (0RV), HUVECs carrying 2 risk variant copies (2RV) showed both depressed baseline and maximum mitochondrial oxygen consumption (p<0.01), and impaired mitochondrial networking on MitoTracker assays. These cells also demonstrated a contracted lysosomal compartment, and an accumulation of autophagosomes suggesting a defect in autophagic flux. Upon blocking autophagy with non-selective lysosome inhibitor, hydroxychloroquine, autophagosome accumulation between 0RV HUVECs and untreated 2RV HUVECs was similar, implicating lysosomal dysfunction in the HRG-associated autophagy defect. Compared to 0RV and 2RV HUVECs, HUVECs carrying 1 risk variant copy (1RV) demonstrated intermediate mitochondrial respiration and autophagic flux phenotypes, which were exacerbated with IFNɣ exposure. Taken together, our data reveal that IFNɣ induces APOL1 expression, and that each additional RV associates with mitochondrial dysfunction and autophagy inhibition. IFNɣ amplifies this phenotype even in 1RV HUVECs, representing the first description of APOL1 pathobiology in variant heterozygous cell cultures.